A strange case involving partial fracture of percutaneous transluminal coronary angioplasty wire and its successful retrieval. Issue 4 (2015) - Sinha, Santosh Kumar; Thakur, Ramesh; Jha, Mukesh Jitendra; Krishna, Vinay; Varma, Chandra Mohan; Tiwari, Pradyot; Mishra, Vikas; Kumar, Ashutosh; Sinha, Rupesh
No abstract available